Molecularly imprinted Co-N-C catalyst as well as preparation method and application thereof
Through the preparation and application of molecularly imprinted Co-N-C catalysts, the problems of high cost of palladium catalysts and insufficient activity of carbon materials in traditional hydrogen peroxide production are solved, and high-efficiency and low-energy consumption of hydrogen peroxide production are achieved, with good stability and application prospects.
Patent Information
- Application Number
- CN202411218749.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
Smart Images

Figure CN119121314A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of two-electron electroreduction to produce hydrogen peroxide, and in particular to a molecularly imprinted Co-NC catalyst and a preparation method thereof and application in high-efficiency electroreduction to produce H2O2. Background Art
[0002] This section merely provides background information related to the present disclosure and is not necessarily prior art.
[0003] Hydrogen peroxide is an oxidant with strong oxidizing ability. It is widely used in energy chemical industry, wastewater treatment and medical industry. It is often used as a bleaching agent and disinfectant in the chemical and medical fields. In the field of wastewater treatment, due to its strong oxidizing property, it has been widely used in the degradation of various pollutants such as dyes, antibiotics, phenols, pesticides, etc.
[0004] The production of hydrogen peroxide mainly relies on the anthraquinone process, which synthesizes hydrogen peroxide through multiple processes such as continuous hydrogenation and oxidation of anthraquinone. In the whole process, toxic and harmful reagents and expensive palladium catalysts are required, and hydrogen peroxide is finally obtained through separation and purification. In addition, the construction of traditional anthraquinone processes often requires high investment costs, and the hydrogen peroxide produced also has high risks in storage and transportation.
[0005] Electrochemical oxygen reduction method through 2e - The partial reduction of O2 by the transfer pathway produces hydrogen peroxide (O2+2H + +2e - →H2O2), which can produce hydrogen peroxide solution in situ in the aqueous phase, and has the advantages of clean, high efficiency, low energy consumption and decentralized production.
[0006] Compared with the high cost of traditional precious metal catalysts, the inertia of carbon materials in oxygen adsorption and the unclear active sites, the present invention uses phthalocyanine molecules to prepare a molecular imprinting catalyst and applies it to the electrogeneration of hydrogen peroxide. Summary of the invention
[0007] Purpose of the invention: The technical problem to be solved by the present invention is to provide a molecularly imprinted Co-NC catalyst and a preparation method and application thereof in view of the deficiencies in the prior art.
[0008] In order to solve the above technical problems, the present invention discloses the following technical solutions:
[0009] In a first aspect, the present invention discloses a molecularly imprinted Co-NC catalyst and a preparation method thereof.
[0010] The catalyst is prepared by directly selecting Co-N4 coordinated phthalocyanine molecules as active sites for loading and utilizing cobalt phthalocyanine and carbon nanotubes.
[0011] The preparation method of the catalyst comprises the steps of pyrolyzing a polymer of aniline and carbon nanotubes, and mixing the obtained pyrolysis product with cobalt phthalocyanine to obtain a molecularly imprinted Co-NC catalyst.
[0012] Specifically, the method comprises the following steps:
[0013] S1: reacting carbon nanotubes CNT and aniline to prepare aniline-carbon nanotube polymer PANI-CNT (NCNT);
[0014] S2: pyrolysis of the obtained aniline-carbon nanotube polymer;
[0015] S3: The product after the pyrolysis in step S2 is mixed with cobalt phthalocyanine CoPc to obtain a molecularly imprinted Co-NC catalyst.
[0016] In step S1, the mass volume ratio of carbon nanotubes to aniline is 1 g:6-7.5 mL, preferably 1 g:6.5-7 mL, preferably 1 g:6.7 mL.
[0017] In step S1, the reaction further includes an acid and an oxidant.
[0018] Furthermore, the acid includes hydrochloric acid and sulfosalicylic acid; the acid is used to provide a protonic acid environment and a proton source, promote the polymerization reaction, and significantly improve the conductivity of polyaniline; the concentration of the acid is 0.05-0.15 mol / L, preferably 0.1 mol / L. In some embodiments, the mass volume ratio of the carbon nanotubes to the acid is 1g:300-400ml, preferably 1g:350ml.
[0019] Furthermore, the oxidant includes ammonium persulfate APS, etc.; in some embodiments, the oxidant is added to the reaction system in the form of an aqueous solution; in some embodiments, the oxidant aqueous solution is added dropwise to the reaction system, and the concentration of the oxidant in the aqueous solution is 0.1-0.3 mol / L, preferably 0.2 mol / L.
[0020] Further, the mixed solution of carbon nanotubes, aniline and acid is stirred to obtain a first reaction solution; an oxidant aqueous solution is added to the first reaction solution until the solution changes color, and the addition of the oxidant aqueous solution is stopped, and stirring is continued to obtain a second reaction solution containing aniline-carbon nanotube polymer NCNT.
[0021] In some embodiments, when the oxidant is ammonium persulfate, an aqueous solution of ammonium persulfate is added to the first reaction solution until the solution turns dark green and then the addition of the oxidant is stopped.
[0022] In some embodiments, the stirring temperature is 20-30°C, preferably 25°C.
[0023] In some embodiments, the mixed solution of carbon nanotubes, aniline and acid is stirred for 0.5-1.5 hours to obtain a first reaction solution, preferably stirred for 1 hour.
[0024] In some embodiments, an aqueous oxidant solution is added to the first reaction solution until the solution changes color, then the addition of the aqueous oxidant solution is stopped and stirring is continued for 0.3-0.7 h, preferably 0.5 h.
[0025] In some embodiments, the second reaction liquid is filtered, the filter cake is washed until colorless, mixed with ammonia water, washed until the pH is 6-8, and dried to obtain aniline-carbon nanotube polymer NCNT.
[0026] In some embodiments, the concentration of the ammonia water is 2%wt-8%wt, preferably 5%wt; after adding the ammonia water, polyaniline and the ammonia water form a collision effect, thereby improving the dedoping efficiency of polyaniline, removing impurities of polyaniline, and improving its purity.
[0027] In some embodiments, the filter cake is washed until colorless and then mixed with aqueous ammonia and stirred for 2.5-3.5 hours, preferably 3 hours; the stirring is carried out at room temperature.
[0028] In some embodiments, the drying temperature is 60-80°C, preferably 70°C; and the drying time is 8-10 hours.
[0029] In step S2, the pyrolysis temperature is 600-1000°C, preferably 700-900°C, preferably 800°C.
[0030] In step S2, the pyrolysis time is 1-3 hours, preferably 2 hours.
[0031] In step S2, the heating rate during the pyrolysis process is 4-6°C / min, preferably 5°C / min; the pyrolysis atmosphere is an inert gas atmosphere.
[0032] In step S3, the mass ratio of the product after pyrolysis in step S2 to cobalt phthalocyanine is 7-8:1, preferably 7.5:1.
[0033] In step S3, the product after pyrolysis in step S2 and cobalt phthalocyanine are dispersed in N,N-dimethylformamide and / or N,N-diethylformamide, and ultrasonicated for 20-40 minutes; after being uniformly mixed, ultrasonicated for 20-40 minutes and stirred to obtain a molecularly imprinted Co-NC catalyst.
[0034] The molecularly imprinted Co-NC catalyst prepared by the above method is also within the protection scope of the present invention.
[0035] In a second aspect, the present invention discloses the use of the molecularly imprinted Co-NC catalyst in catalyzing oxygen reduction to prepare hydrogen peroxide.
[0036] The application is electrosynthesis of hydrogen peroxide, and further is production of hydrogen peroxide by two-electron electroreduction.
[0037] In some embodiments, the current density during the application is 90-110 mA cm -2 , such as 95, 100, 105mAcm -2 .
[0038] In some embodiments, the pH during the application process is 5-8, such as 6 or 7.
[0039] In some embodiments, the aeration rate during the application process is 0.1-0.3 L / min, such as 0.2 L / min.
[0040] In some embodiments, the electrolyte in the application process includes Na2SO4.
[0041] Beneficial effects:
[0042] 1. The catalyst provided by the present invention can efficiently produce hydrogen peroxide. -2 Under the conditions of pH=7, the yield reached 261.04mmol / L in 8 hours.
[0043] 2. The catalyst prepared by the present invention also exhibits a good H2O2 yield under the condition of very low oxygen aeration amount (0.2L / min).
[0044] 3. The stability of the catalyst provided by the present invention can reach 8 hours, the properties are relatively stable, and it has high application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0046] Figure 1 X-ray diffraction patterns (XRD) of CoPc-NCNT, CoPc-CNT, NCNT, and CNT catalysts.
[0047] Figure 2 SEM images and mapping diagrams of CoPc-NCNT, CoPc-CNT, NCNT, and CNT catalysts.
[0048] Figure 3 Rotating ring disk electrode voltammograms (RRDE) of CoPc-NCNT, CoPc-CNT, NCNT, and CNT catalysts.
[0049] Figure 4 The hydrogen peroxide production and stability of CoPc-NCNT catalyst.
[0050] Figure 5 is the hydrogen peroxide production of CoPc-NCNT, CoPc-CNT, NCNT, and CNT catalysts. DETAILED DESCRIPTION
[0051] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.
[0052] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0053] Example 1
[0054] This embodiment provides a method for preparing a molecularly imprinted catalyst, and the specific steps are as follows:
[0055] In the first step, take 35ml of 0.1mol / L HCl in a beaker, weigh 0.1gCNT and add it, take 0.67ml aniline and add it to the above beaker, put it in a water bath, and stir it at a constant temperature of 25℃ for 1h. Weigh 1.52g of ammonium persulfate and dissolve it in 35ml deionized water. After it is fully dissolved, drip it drop by drop into the beaker containing CNT, observe the change in the color of the solution, stop dripping when the solution turns dark green, and continue stirring for 30min. Filter the polymerized product and wash it with deionized water 3-4 times until the filtrate is colorless. Then put the filter cake into 100ml5%wt ammonia water, stir for 3h, and then wash it with deionized water until the pH is 6-8. Put the filter cake into an oven at 70℃ and dry it for 8h. The product PANI-CNT (NCNT) is obtained.
[0056] In the second step, the dried NCNT was placed in a tube furnace and pyrolyzed at 800°C for 2h at a heating rate of 5°C / min. 60mg of pyrolyzed NCNT and 8mg of CoPc were weighed and added to 20ml of DMF solution respectively, and ultrasonicated for 30min in an ultrasonic machine, and then the two solutions were mixed and ultrasonicated for 30min. After the ultrasonication, it was placed in a constant temperature water bath and stirred for 8h, and the obtained product was placed in a freeze dryer to obtain the final product CoPc-NCNT.
[0057] Comparative Example 1
[0058] This comparative example is used for comparison with Example 1. The main process is as follows: CNT is placed in a tubular furnace and pyrolyzed at 800°C for 2h with a heating rate of 5°C / min. 60mg of pyrolyzed CNT and 8mg of CoPc are weighed and added to 20ml of DMF solution respectively, and ultrasonicated for 30min in an ultrasonic machine, and then the two solutions are mixed and ultrasonicated for 30min. After the ultrasonication, it is placed in a constant temperature water bath and stirred for 8h, and the obtained product is placed in a freeze dryer to obtain the final product CoPc-CNT.
[0059] Comparative Example 2
[0060] This comparative example is used for comparison with Example 1. The main process is as follows: Take 35ml 0.1mol / L HCl in a beaker, weigh 0.1gCNT and add it, take 0.67ml aniline and add it to the above beaker, put it in a water bath, and stir it at a constant temperature of 25°C for 1h. Weigh 1.52g ammonium persulfate and dissolve it in 35ml deionized water. After fully dissolving, drip it drop by drop into the beaker containing CNT, observe the change in the color of the solution, stop dripping when the solution turns dark green, and continue stirring for 30min. The polymerized product is filtered out and washed with deionized water 3-4 times until the filtrate is colorless. Then put the filter cake into 100ml5%wt ammonia water, stir for 3h, and then wash with deionized water until the pH is 6-8. Put the filter cake into an oven at 70°C and dry it for 8h. The product PANI-CNT (NCNT) is obtained.
[0061] Comparative Example 3
[0062] This comparative example is used for comparison with Example 1, and the main process is as follows: commercial CNTs are taken, placed in a tubular furnace, pyrolyzed at 800° C. for 2 h, with a heating rate of 5° C. / min, to obtain product CNTs.
[0063] Experimental example
[0064] 1. XRD phase characterization
[0065] X-ray diffraction (XRD) was used to characterize the physical phases of CoPc-NCNT, CoPc-CNT, CoPc, NCNT and CNT.
[0066] 2. Microscopic Characterization
[0067] Scanning electron microscopy (SEM) was used to characterize the morphology of CoPc-NCNT.
[0068] 3. Electrochemical Characterization
[0069] All catalyst electrochemical tests were completed using Shanghai Chenhua CHI760E electrochemical workstation.
[0070] The catalytic performance of the catalyst was characterized using a conventional three-electrode system, with a rotating ring disk electrode as the working electrode, a high-purity stone grinding rod as the counter electrode, and a silver-silver chloride electrode as the reference electrode. Before use, the rotating ring disk electrode was initially polished with 0.3 μm alumina polishing powder on a nylon cloth, and then further polished with 0.05 μm alumina polishing powder after cleaning.
[0071] Preparation of catalyst slurry: 5 mg CoPc-NCNT was dispersed in 50 μL Nafion, 0.5 ml anhydrous ethanol, and 2.5 mg super P was added. The CoPc-NCNT slurry was obtained by ultrasonic treatment for 1 h. 10 μL of the slurry was drop-coated on the treated RRDE and waited for it to dry completely. The working electrode was then prepared. The slurries corresponding to the other three materials were prepared in the same way.
[0072] Preparation of electrode: Take 1 g of CoPc-NCNT, add 25 ml of ethanol and 1 ml of PTFE, stir and ultrasonicate until the catalyst aggregates into agglomerates.
[0073] The steps of the ORR test process are: 1) The electrochemical test system is a three-electrode system (glassy carbon electrode as the working electrode, carbon rod as the counter electrode, Ag / AgCl as the reference electrode), and the electrolyte is a 0.1 mol / L Na2SO4 solution. 2) Before the test, oxygen is continuously introduced into the reactor for 20 minutes to ensure that the electrolyte solution reaches oxygen saturation. The ventilation flow rate is 150-250 mL / min, and oxygen must be continuously introduced during the test. 3) To evaluate the oxygen reduction catalytic activity, a polarization curve test (LSV) is required: the voltage scanning range is -0.8-0.2 V vs. Ag / AgCl, the scanning speed is 1 mV / s, and the rotation speed is 1600 rpm;
[0074] Hydrogen peroxide yield test: at a current density of 100 mA cm -2 Under the conditions of pH 7 and aeration volume of 0.2 L / min, the catalyst electrode sheet was used as the working electrode, the carbon rod was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The cumulative concentration of hydrogen peroxide was recorded in 0.1 M Na2SO4 electrolyte.
[0075] 4. Results
[0076] Figure 1 : X-ray diffraction patterns (XRD) confirmed that CoPc-NCNT, CoPc-CNT, NCNT, and CNT had characteristic peaks corresponding to cobalt phthalocyanine molecules and carbon materials, confirming that the four materials were successfully synthesized.
[0077] Figure 2 : From the SEM and Mapping images of CoPc-NCNT, it can be seen that Co is evenly dispersed without agglomeration.
[0078] Figure 3 :The rotating ring-disk electrode test shows that the disk current density of CoPc-NCNT is 2.46 mA cm -2 , which belongs to the disk current characteristics of a two-electron hydrogen peroxide production catalyst, and calculated by the KL equation, the electron transfer numbers of the four materials CoPc-NCNT, CoPc-CNT, NCNT, and CNT are 2.32, 2.57, 2.73, and 3.06, respectively. It can be seen that the electron transfer number of the CoPc-NCNT provided by the present invention is closer to 2, and the ability to produce hydrogen peroxide is stronger than that of the other three materials.
[0079] Figure 4 : At 100mA cm -2 The yield and stability of hydrogen peroxide were studied at a current density of 1.8 V. The voltage was stable at 1.8 V within 8 h, and then began to rise. At this time, the cumulative concentration of hydrogen peroxide reached 261.04 mmol / L, and the average yield reached 6.52 mol g -1 h -1 .
[0080] Figure 5 : At 100mAcm -2 The cumulative concentrations of hydrogen peroxide produced by the four materials at different times were compared under current densities.
[0081] The molecularly imprinted Co-NC catalyst disclosed in the present invention is obtained by polymerizing carbon nanotubes into a mixture of aniline and hydrochloric acid to obtain NCNT, which is then pyrolyzed at high temperature, and then the cobalt phthalocyanine molecules and NCNT are impregnated and freeze-dried to obtain the final catalyst. The phthalocyanine molecules used in the present invention can be highly dispersed on the surface of nitrogen-doped carbon nanotubes, and their own Co-N coordination is stable. The preparation process of the entire catalyst is convenient. When the catalyst is used for electrochemical reduction to prepare hydrogen peroxide, it has high activity and high yield, can effectively reduce oxygen to hydrogen peroxide, and the cumulative output reaches 261.04mmol / L, which meets the actual application scenario and has good application prospects.
[0082] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a catalyst, characterized in that: The steps include: S1: subjecting carbon nanotubes and aniline to polymerization reaction to prepare aniline-carbon nanotube polymer; S2: pyrolysis of the obtained aniline-carbon nanotube polymer; S3: The product after the pyrolysis in step S2 is mixed with cobalt phthalocyanine to obtain a catalyst.
2. The method according to claim 1, characterized in that In step S1, the mass volume ratio of carbon nanotubes to aniline is 1 g:6-7.5 mL, preferably 1 g:6.5-7 mL.
3. The method according to claim 1, characterized in that In step S1, the reaction further includes an acid and an oxidant; the concentration of the acid is 0.05-0.15 mol / L, and the mass volume ratio of the carbon nanotubes to the acid is 1 g:300-400 ml; the oxidant is added to the reaction system in the form of an oxidant aqueous solution; the concentration of the oxidant aqueous solution is 0.1-0.3 mol / L.
4. The method according to claim 1 or 3, characterized in that: In step S1, a mixed solution of carbon nanotubes, aniline and acid is stirred at 20-30°C for 0.5-1.5h to obtain a first reaction solution; an oxidant aqueous solution is added to the first reaction solution until the solution changes color, then the addition of the oxidant aqueous solution is stopped, and stirring is continued for 0.3-0.7h to obtain a second reaction solution containing aniline-carbon nanotube polymer.
5. The method according to claim 4, characterized in that The second reaction liquid is filtered, the filter cake is washed until colorless, mixed with ammonia water and stirred for 2.5-3.5h, washed until the pH is 6-8, and dried to obtain aniline-carbon nanotube polymer NCNT; preferably, the concentration of ammonia water is 2%wt-8%wt.
6. The method according to claim 1, characterized in that In step S2, the pyrolysis temperature is 600-1000°C, preferably 700-900°C; preferably, the pyrolysis time is 1-3h; preferably, the heating rate during the pyrolysis process is 4-6°C / min.
7. The method according to claim 1, characterized in that In step S3, the mass ratio of the product after pyrolysis in step S2 to cobalt phthalocyanine is 7-8:1, preferably 7.5:
1.
8. The method according to claim 1, characterized in that In step S3, the product obtained after the pyrolysis in step S2 and cobalt phthalocyanine are dispersed in a solvent respectively, and ultrasonicated for 20-40 minutes; after being uniformly mixed, ultrasonicated for 20-40 minutes is continued, and stirred to obtain a catalyst.
9. The catalyst prepared by the method according to any one of claims 1 to 8.
10. Use of the catalyst according to claim 9 in catalyzing oxygen reduction to produce hydrogen peroxide.
